Protective effects of vitamin E forms (alpha-tocopherol, gamma-tocopherol and d-alpha-tocopherol polyethylene glycol 1000 succinate) on retinal edema during ischemia-reperfusion injury in the guinea pig retina - Aydemir, Orhan; Çelebi, Serdal; Yılmaz, Turgut; Yekeler, Hayrettin; Kükner, A. Şahap (Kluwer Academic Publishers, 2004)
Purpose: The purpose of this study is to provide evidence that free radical damage is a component of retinal ischemia-reperfusion (I/R) injury, and to determine whether alpha-tocopherol, gamma-tocopherol and d-alpha-tocopherol polyethylene glycol 1000 succinate (TPGS) can protect the retina from this injury. Methods: The right eyes of 40 male guinea pigs weighing 500-600 g were used. The animals were randomly assigned to group 1 (control), group 2 (I/R), group 3 (I/R plus alpha-tocopherol), group 4 (I/R plus gamma-tocopherol) and group 5 (I/R plus TPGS). Groups 3, 4 and 5 received four subcutaneous injections at six-hour intervals for total dosage of 800 IU/kg alpha-tocopherol, 1000 IU/kg gamma-tocopherol and 750 IU/kg TPGS, respectively. The first dose of each substance was administered 5 minutes before retinal ischemia. Retinal ischemia was induced for 90 minutes, then followed by reperfusion for 24 hours. Injections of three substances were repeated at 6, 12 and 18 hours during reperfusion. The animals were killed at 24 hours of reperfusion. Sagittal sections of 4 ?m were cut and stained with hematoxylin and eosin for light microscopic evaluation. The average thickness (edema) of the inner plexiform layer for each eye was measured in sagittal sections near the optic nerve and expressed in microns. Results: All the three substances showed statistically significant protection against the formation of retinal edema during ischemia-reperfusion injury. The mean thickness of the inner plexiform layer were 15.0, 25.44, 19.81, 21.38 and 20.88 ?m in control, I/R, I/R plus alpha-tocopherol, I/R plus gamma-tocopherol and I/R plus TPGS groups, respectively. The results showed that the thickness of the inner plexiform layer in group 1 (control) was significantly lower than the other groups (p <0.001). The inner plexiform layer was thicker in the I/R group than with I/R plus alpha-tocopherol (p <0.001), I/R plus gamma-tocopherol (p <0.001) and I/R plus TPGS (p <0.01). The inner plexiform layer was not thicker in the I/R plus TPGS group than in the I/R plus alpha-tocopherol and I/R plus gamma-tocopherol groups. Compared to the I/R plus alpha-tocopherol group, the inner plexiform layer was significantly thicker in the I/R plus gamma-tocopherol group (p <0.01). Conclusions: The results from these experiments indicate that vitamin E forms have protective effects on the retina during retinal ischemia-reperfusion injury, but, the effects of alpha-tocopherol and TPGS appear to be much greater than that of gamma-tocopherol. © Springer 2006.
Keywords: Alpha-tocopherol; Gamma-tocopherol; Ischemia-reperfusion injury; Retina; TPGS